2008
DOI: 10.1016/s1808-8694(15)30576-0
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Immittance in children without otoacoustic emissions

Abstract: tympanometry associated with acoustic reflex adds accuracy to the diagnosis of middle ear abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
5
2
Order By: Relevance
“…A study comparing TOAE and tympanometry results with infants with no hearing loss risk indicators showed a greater proportion of tympanometric alteration in the group of infants with absence of TOAE, 21 corroborating the findings of our study. Otitis media with effusion is often asymptomatic and can go unnoticed owing to its symptoms being less evident than those of acute otitis media.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study comparing TOAE and tympanometry results with infants with no hearing loss risk indicators showed a greater proportion of tympanometric alteration in the group of infants with absence of TOAE, 21 corroborating the findings of our study. Otitis media with effusion is often asymptomatic and can go unnoticed owing to its symptoms being less evident than those of acute otitis media.…”
Section: Discussionsupporting
confidence: 91%
“…20 Tympanometry consists of checking the mobility of the tympanic-ossicular system through the variation introduced into the external auditory meatus, being effective in the early identification of middle ear disorders. 20,21 Recurrent otitis and diseases that affect the middle ear are very common in children and infants and this is why tympanometry was used in the hearing screenig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, for newborns in Group I, the mean ASRT obtained with the 226 Hz probe was lower (Table 1) in all frequencies in comparison to that found by other studies (14,24) . With the 1,000 Hz probe, the average was 74.2 dB for the 1,000 Hz frequency and 62.9 dB for 2,000 Hz (Table 1).…”
Section: Discussioncontrasting
confidence: 72%
“…43 There was no significant difference between gender and frequency. A study (24) observed newborns and the association between Transient-Evoked Otoacoustic Emission (TEOAE) and changes in acoustic immittance with a 226 Hz probe. For that, the authors assessed 20 newborns with absent TEOAEs (experimental group) and 101 with TEOAEs (study group).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Consequently, abnormal ME status is an important cause of absent or diminished OAEs in newborns undergoing hearing screening. Conversely, newborns that fail the OAE screening tests are more likely to have abnormal acoustic immittance test outcomes, 5 with 50% of newborn ears failing OAE tests reportedly having ME effusion or dysfunction. 6 Approximately four per 1,000 newborns had ME pathology with or without conductive hearing loss in one study.…”
Section: Introductionmentioning
confidence: 99%